(untitled) (GIST – Education and Learning Research Journal, 2020)
Abstract This paper reports an action research study on cooperative learning projects for engineering students at a public university. The study is aimed at improving reading skills through the use of four cooperative learning projects implemented during the English classes. Information gathered from a survey, a group’s interviews, and the teacher’s journal was collected and analyzed to determine the categories after being coded. Findings suggest that students significantly enhanced their reading skills by working cooperatively. Conclusions also highlight the notion that cooperative learning strengthens English reading skills and fosters leadership, decision making, communication and problem-solving abilities. Additionally it increases participation, motivation and goal achievement in Students language learning process.